P75-F Evaluation of deterioration in sensory nerve conduction studies in Amyotrophic Lateral Sclerosis. Issue 7 (July 2019) - Gunes, Taskin; Sirin, Gorkem; Isak, Baris
Abstract : Background: Many neurophysiological and pathological studies showed sensory abnormalities in ALS patients as a part of multisystem disease. In this study, we assessed progression of sensory changes in ALS patients, using nerve conduction studies (sNCS) in two consecutive visits. Material and methods: sNCSs were evaluated based on amplitudes and velocities of bilateral dorsal sural (DS), medial plantar, superficial peroneal (SP), sural and left radial sensory nerves. In addition a global Total Sensory Score (TSens) was determined using the amplitudes of these nerves. Results: Although, for both visits, TSens was smaller in patients ( p  = 0.04 and P  = 0.01, for consecutive visits) then controls, there was no significant change between two visits of the patients ( P  = 0.19). ALS patients had significantly smaller amplitudes and slower velocities for bilateral DS, and left radial nerves for both visits. TSens was reduced in 7 (63.3%) but increased in 4 (36.6%) ALS patients. Conclusions: Although, ALS patients showed considerable changes in NCS, sensory denervation is probably slowly progressive. The patients with improved sNCS were attributed to possible changes in sensory nerve excitability following corrective measures, e.g. administration of parenteral gastrostomy or high caloric diet.